2016
DOI: 10.1186/s13046-016-0454-4
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 integration probably contributes to cervical oncogenesis through interrupting tumor suppressor genes and inducing chromosome instability

Abstract: BackgroundThe integration of human papilloma virus (HPV) into host genome is one of the critical steps that lead to the progression of precancerous lesion into cancer. However, the mechanisms and consequences of such integration events are poorly understood. This study aims to explore those questions by studying high risk HPV16 integration in women with cervical intraepithelial neoplasia (CIN) and cervical squamous cell carcinoma (SCC).MethodsSpecifically, HPV integration status of 13 HPV16-infected patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…Alterations like these could promote cervical cancer carcinogenesis. Previous studies have also shown that HPV integration causes DNA damage and repair, thereby leading to genomic instability [ 8 ]. The presence of gene deletions and insertions near HPV integration loci in cervical cancer cell lines and clinical samples suggests that genome instability caused by HPV integration, which can disrupt gene expression, may be a hallmark of cervical cancer [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations like these could promote cervical cancer carcinogenesis. Previous studies have also shown that HPV integration causes DNA damage and repair, thereby leading to genomic instability [ 8 ]. The presence of gene deletions and insertions near HPV integration loci in cervical cancer cell lines and clinical samples suggests that genome instability caused by HPV integration, which can disrupt gene expression, may be a hallmark of cervical cancer [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the persistence of a viral genome in its host cells can lead to genomic instability, overexpression of oncogenes or repression of tumour suppressor genes. For instance, HPV16 integration is responsible for occasional chromosomal translocation in cervical intraepithelial neoplasia, EBV persistence both mediates the oncogene c‐myc overexpression and the occurrence of the translocation t(8;14), arguing for a direct role and/or a synergetic role of EBV in cell transformation in Burkitt lymphoma. Moreover, viruses can also produce genomic instability when impairing the DNA repair systems such as the nonhomologous end joining (NHEJ) in host cells, which is a hallmark of all types of soft tissue sarcoma such as DFSP: in early stages of Kaposi sarcoma, HHV‐8 interferes with the NHEJ of the host cells through a processivity factor (PF‐8) .…”
Section: Viral Contiguous Sequences (Contigs; Genomic Sequences Obtaimentioning
confidence: 99%
“…For virus integration to occur, the circular viral genome needs to be linearized. In most cases, the viral non-coding region (ncr) and the viral oncogenes E6 and E7 remain intact whereas the E1 or E2 regions are frequently disrupted [6][7][8]. This event either uncouples the E2 gene from the viral promoter p97 or leads to functional inactivation of the affected viral gene itself.…”
Section: Introductionmentioning
confidence: 99%